Triglyceride and glucose index is a simple and easy‐to‐calculate marker associated with nonalcoholic fatty liver disease. Issue 6 (8th June 2022) - Kim, Kyung‐Soo; Hong, Sangmo; Ahn, Hong‐Yup; Park, Cheol‐Young
Abstract: Objective: The aim of this study was to evaluate the relationship between the triglyceride and glucose (TyG) index and nonalcoholic fatty liver disease (NAFLD) using a large, population‐based cohort study database. Methods: A total of 52, 575 participants were enrolled from 2007 to 2013 in the Kangbuk Samsung Health Study cohort. The presence of NAFLD was ascertained by ultrasonography in the absence of other known liver diseases. Results: Over a median 5.1 years of follow‐up, 7, 292 participants (13.87%) were diagnosed with NAFLD. In a multivariate‐adjusted model, the hazard ratio for NAFLD of the TyG index was 1.413 (95% CI: 1.349‐1.480) in the first 6 months, 1.480 (95% CI: 1.408‐1.556) in months 6 to 12, 1.427 (95% CI: 1.370‐1.485) in months 12 to 18, and 1.246 (95% CI: 1.159‐1.339) in months >18. The hazard ratios of triglycerides, glucose, fatty liver index, and homeostatic model assessment of insulin resistance for NAFLD in months >18 were 1.124 (95% CI: 1.061‐1.190), 1.037 (95% CI: 0.970‐1.109), 1.508 (95% CI: 1.417‐1.605), and 1.177 (95% CI: 1.116‐1.242), respectively. The NAFLD‐free rate decreased with increasing TyG index quartile ( p < 0.001). The TyG index level from which the risk of NAFLD increased appeared to be 8.24. Conclusions: This study found that the TyG index is a simple and easy‐to‐calculate marker associated with NAFLD.